PTU-020 Endoscopy-related litigation in UK: causes, costs and outcome. (23rd September 2015) - Sheikh, K; Webster, G
Abstract : Introduction: When endoscopy-related complications occur, patients may seek legal redress. Although the majority of complaints in the UK are resolved locally by NHS Trusts, since its inception in 1995 approx 4% of cases referred to the NHS litigation authority (NHSLA) required settlement in the court. Aims: To investigate the annual frequency of endoscopy-related claims, the endoscopic procedures and complications that result, and the outcome of claims handled by NHSLA. To assess how these claims may inform risk management strategies. Methods: A search of the computerised NHSLA database was undertaken to extract the endoscopy related claims handled between 1995 and 2008. Search keywords used were "endoscopy", "ERCP", "colonoscopy", "gastroscopy" and "PEG". Details available included year of incident and claim, incident summary, clinical outcome, success/failure of claim, and financial settlement. Results: 418 endoscopy-related negligence claims submitted to NHSLA during this period, which comprised 17% of total NHSLA claims requiring settlement in court. Of 353 claims that have been settled to date, 175 (49.6%) were successful, resulting in total costs of £6 773 686 and 178 (51.4%) were unsuccessful but still incurred legal costs of £258 656. Claims reached a peak in 2002–2003. Upper GI endoscopy and colonoscopy were associated with 65% of settled claims, but ERCP was the procedure most frequently linked to the 74/353 (21%) of claims related to a fatal outcome. Factors underlying claims following fatal complications included: inappropriate endoscopic treatment/direct complication (51%); delay in recognising complication±its management (39%); consent issues (6%); and medication issues (4%), including incorrect management of anticoagulation. Conclusion: As >500 000 endoscopies/year are performed in UK, the proportion of endoscopies that result in court proceedings through the NHSLA is tiny but the relative human and financial cost is high. Although the data suggest that claims are falling this may be misrepresentative, as claims can be made several years after the incident and the NHSLA has recently revised policies. Although successful claims resulted from direct endoscopic complications (eg, perforation, haemorrhage), many related to delays in the diagnosis and appropriate management of endoscopic complications, with adverse, and sometimes fatal, consequences. The findings may further inform the need for robust systems within endoscopy units to identify early and in particular late endoscopic complications.